Influence of annual atmospheric precipitation on the potential for sand encroachment on roads (Международный научный журнал «Инженер», 2026)
This article investigates the correlation between the potential for sand encroachment on a newly constructedrailway line and the annual precipitation levels. An expert survey was conducted among specialists directly andindirectly involved with this issue, alongside a statistical analysis of natural and climatic winter-springprecipitation over several years in regions where the under-construction railway intersects dune sands. Theannual precipitation data were compared with the occurrence of sand drifts. The results of the expert survey,monitoring of potential railway sand encroachment, and precipitation analysis are presented. It was establishedthat the manifestation of sandstorms, and consequently the potential for sand encroachment on infrastructure, isdependent on the amount of rainfall during the winter-spring period. Utilizing the findings of this research willenable the elimination of unnecessary annual measures for protecting the new railway line from sand drifts,specifically those related to the stabilization of mobile sands.